Women's Representation and Public Spending - Helena Svaleryd (Research Institute of Industrial Economics (IFN), 2007)
This paper studies whether the degree of womens representation in Swedish local councils affects local public expenditure patterns. Theoretically, the individual preferences of elected representatives may have an impact on public expenditure if full policy commitment is not feasible. To empirically address the question, I first analyze the preferences expressed by elected local council representatives using survey data. This permits me to make precise predictions about the effects of womens representation on spending. The subsequent panel study on the composition of public spending in Swedish municipalities supports the predictions derived from the survey.
Keywords: C23; C25; D78; H40; J16; 330; Political Representation; Local Public Expenditure; Gender; Survey Data; Panel Data; Politiker; Frauen; Kommunalpolitik; Kommunale Ausgaben; Schweden